Rhizosphere Growth-Promoting Fungi of Healthy Nicotiana tabacum L.: A Systematic Approach to Boosting Plant Growth and Drought Resistance - Quanyu Yin; Zhao Feng; Zhichao Ren; Ao Li; Amit Jaisi; Mengquan Yang (Microorganisms)
Drought, exacerbated by global warming, poses a significant threat to crop growth and productivity. This study identified a strain of Trichoderma harzianum from the rhizosphere of healthy Nicotiana tabacum L. plants and evaluated its role in enhancing drought tolerance. The isolated strain effectively colonized plant roots and promoted the growth of N. tabacum L. To investigate its potential, T. harzianum was inoculated into plants under varying drought conditions, and its impact on growth, physiological responses, and drought resilience was assessed. Comprehensive analyses of agronomic traits, physiological parameters, enzyme activities, photosynthetic performance, osmoprotectant levels, and membrane lipid peroxidation revealed that T. harzianum inoculation (light drought with T. harzianum, moderate drought with T. harzianum, and severe drought with T. harzianum treatments) systematically improved plant development and drought resistance. These findings provide valuable insights and lay a foundation for developing innovative biofertilizers to enhance crop drought tolerance and sustainability.